2007
DOI: 10.1515/epoly.2007.7.1.461
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of functional nanostructures sputtered on polypropylene nonwovens

Abstract: Functional nanocomposite nonwoven materials were prepared by surface coating with copper and silver using magnetron sputter coating. The composite nonwoven materials with metallic nanostructures were analyzed and compared by means of atomic force microscopy, energy dispersive X-ray analysis and electrical and optical tests. The observations by atomic force microscopy revealed the formation of functional nanostructures on the fibre surfaces. It was found that copper had more compact structures on the fiber surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…As more silver species arrive, the originally separated silver seeds will grow and eventually connect to neighbouring ones. As a result of this kind of growth, a continuous layer of Ag polycrystals forms on the fibre surface; (2) Such bombardments probably scatter ion [13] and/or break the original chemical or absorbed bonds of the atoms/molecules on the substrate surface, which can change molecular degrees [18] and interface-phase structures between silver and the surface of the organic material [19], causing the ions to diffuse and/or depart out from the fibres. The effect not only baffles and retards further-arrived silver species to be adhered or adsorbed, but also has opportunity to break silver-silver crystal bonds to form boundaries, or to cleave nanocrystal grains into smaller ones, or break the silver-fibre bonds to desquamate silver coating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As more silver species arrive, the originally separated silver seeds will grow and eventually connect to neighbouring ones. As a result of this kind of growth, a continuous layer of Ag polycrystals forms on the fibre surface; (2) Such bombardments probably scatter ion [13] and/or break the original chemical or absorbed bonds of the atoms/molecules on the substrate surface, which can change molecular degrees [18] and interface-phase structures between silver and the surface of the organic material [19], causing the ions to diffuse and/or depart out from the fibres. The effect not only baffles and retards further-arrived silver species to be adhered or adsorbed, but also has opportunity to break silver-silver crystal bonds to form boundaries, or to cleave nanocrystal grains into smaller ones, or break the silver-fibre bonds to desquamate silver coating.…”
Section: Resultsmentioning
confidence: 99%
“…Silver is thus a preferred coating material because of its outstanding electrical properties and competitive price. Besides antimicrobial activity of silver coatings on fabrics [11,13], silver coated fabrics have a great potential in becoming wearable electrodes for medical treatments and measurements. However, the difference of the thermal and mechanical properties between silver and polymers is a challenging problem.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of hydrogen (H) in the material is too light to be detected in the EDX analysis. 10 Two clear peaks of Ti in the EDX spectrum after the TiO 2 coatings of 20, 60, and 100 nm can be seen in Figs. 3b, 3c, and 3d, respectively.…”
Section: Edx Analysismentioning
confidence: 91%
“…[14] It has been shown that the morphology and electrical properties of the metalized polypropylene depend on the thickness of the metal layer. [15] Surface morphology, the mechanical and electrical properties of thin metal films on polymers are all of primary importance for the functionality of these structures in different applications. [16 -19] Migration and aggregation of metal atoms on metal-polymer interface, which can be affected by deposition conditions, are also of great importance.…”
Section: Introductionmentioning
confidence: 99%